Family bonding and children's altruism. - Law, Xue Fen. (2012)
The purpose of this paper is to investigate the nurture aspect of altruism, in other words the correlation between the intensity of family bonding and the level of altruism displayed in children. As such, this paper conducts a series of experimental games involving the Dictator’s Game and Ultimatum Game to observe the extent of altruistic behaviours displayed by children aged 4 to 6, in the local context. On the other hand, data gathered from the questionnaires will serve to examine the structure and degree of family bonding. Based on the analysis of the results, we find that children value fairness and egalitarianism. Their altruistic behaviours are more significantly affected by fair norm exhibited by their peers in the classroom context, rather than the intensity of family bonding. This paper aims to gain a deeper understanding of the correlation, as well as, to promote awareness of the importance of family bonding, and ultimately towards building a better society for fellow Singaporeans.